Endoscopic “String Sign” - Espinel, Jesus; Pinedo, Eugenia; Rascarachi, Gabriela; Ojeda, Vanesa (JOP. Journal of the Pancreas, 2014)
No abstract available. Image: Mucus excretion from a “fish-mouth” look-like patulous papilla